Monoclonal antibody as an emerging therapy for acute ischemic stroke - Woods, Demi (Int J Physiol Pathophysiol Pharmacol, 2020)
Acute ischemic stroke (AIS) is the 5(th) leading cause of death and the leading cause of neurological disability in the United States. The oxygen and glucose deprivation associated with AIS not only leads to neuronal cell death, but also increases the inflammatory response, therefore decreasing the functional outcome of the brain. The only pharmacological intervention approved by the US Federal Food and Drug Administration for treatment of AIS is tissue plasminogen activator (t-PA), however, such treatment can only be given within 4.5 hours of the onset of stroke-like symptoms. This narrow time-range limits its therapeutic application. Administrating t-PA outside of the therapeutic window may induce detrimental rather than beneficial effects to stroke patients. In order to reduce the infarct volume of an AIS while increasing the time period for treatment, new treatments are essential. Emerging monoclonal antibody (mAb) therapies reveal great potential by targeting signaling pathways activated after an AIS. With successful application of mAb in the treatment of cancer, other therapeutic uses for mAb are currently being evaluated. In this review, we will focus on recent advances on AIS therapy by using mAb that targets the signaling cascades and endogenous molecules such as inflammation, growth factors, acid-sensing ion channels, and N-methyl-D-aspartate receptors. Therefore, developing specific mAb to target the signaling pathways of ischemic brain injury will benefit patients being treated for an AIS.